Reversible posterior leukoencephalopathy syndrome and anti-neoplastic agents: a review - Farheen M. Shah-Khan; Daryl Pinedo; Prabodh Shah (Frontiers Media S.A., 2011)
Reversible Posterior Leukoencephalopathy Syndrome (RPLS) is a well recognized entity with a variety of benign and malignant conditions. Recently it has been found to be associated with the use of anti-neoplastic agents including targeted therapies. RPLS occurs rapidly with the use of some drugs and more slowly with others. Combined therapies are associated with a more frequent and more rapid presentation. This review was based on a literature search for English Language articles concerning RPLS and chemotherapeutic agents published from June 1996 to March 2007. We used the PubMed database with keywords: "RPLS", "Posterior reversible encephalopathy syndrome", "(PRES)", "Chemotherapy" and "MRI". This syndrome has classical Clinical-Radiologic features that are easy to recognize. Early recognition and withdrawal of the offending agent is all that is needed in most cases. This review highlights the features of the syndrome. It draws our attention to an entity which is being more frequently recognized and whose exact pathologic mechanisms need to be further studied. This syndrome is associated with the use of neurotoxic as well as non-neurotoxic agents and usually runs a benign course if there is an early diagnosis and management.